2019
DOI: 10.3390/app9081531
|View full text |Cite
|
Sign up to set email alerts
|

Active Control of Broadband Noise Inside a Car Using a Causal Optimal Controller

Abstract: This paper investigates active broadband noise control inside vehicles with a multichannel controller. The noncausal inversion of a practical nonminimum-phase secondary path is formulated, and its influence on noise-reduction performance is analyzed. Based on multiple coherence between reference signals and undesired noise, a novel formulation for identifying primary paths with correlated excitation signals is presented and a causal optimal controller is proposed. Meanwhile, the proposed controller can be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Through a large number of research and analysis, it is found that the excitation frequency that can cause vehicle cab vibration to generate interior noise is about 10∼300 Hz (Guo et al, 2019). Among them, the vibration noise generated mainly by the overall structure of the cab is approximately in the frequency range of 10∼30 Hz, and the interior noise generated mainly by the metal wall panels of the cab is approximately in the frequency range of 30∼200 Hz (Abouel-Seoud, 2019; Zhang et al, 2018; Zhu et al, 2019). Usually below 250 Hz, the structural noise of the automobile is dominant (Mohanty et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Through a large number of research and analysis, it is found that the excitation frequency that can cause vehicle cab vibration to generate interior noise is about 10∼300 Hz (Guo et al, 2019). Among them, the vibration noise generated mainly by the overall structure of the cab is approximately in the frequency range of 10∼30 Hz, and the interior noise generated mainly by the metal wall panels of the cab is approximately in the frequency range of 30∼200 Hz (Abouel-Seoud, 2019; Zhang et al, 2018; Zhu et al, 2019). Usually below 250 Hz, the structural noise of the automobile is dominant (Mohanty et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A problem with using equation (17a) to determine the filter coefficients is that they will result in acausal filters (Zhu et al, 2019) because of the time delay in the physical system between the inputs to the shakers and the measured responses from the low–pass-filtered accelerometer signals. To compensate for this delay, a pure time delay normalΔ is added to the reference signal boldx to give the desired signal dk, (k=1,2).…”
Section: The Control Systemmentioning
confidence: 99%
“…Other types of noise sources, such as road noise, have a broadband nature but have some characteristics independent of the vehicle speed. In this case, also to limit stability problems, the main strategy regards the use of fixed precalculated filter coefficients [7,16]. Some more innovative algorithms can be found in the literature [17], but they are limited to experimental tests in the laboratory.…”
Section: Introductionmentioning
confidence: 99%